2022
DOI: 10.1038/s41467-022-31710-9
|View full text |Cite
|
Sign up to set email alerts
|

Probing strigolactone perception mechanisms with rationally designed small-molecule agonists stimulating germination of root parasitic weeds

Abstract: The development of potent strigolactone (SL) agonists as suicidal germination inducers could be a useful strategy for controlling root parasitic weeds, but uncertainty about the SL perception mechanism impedes real progress. Here we describe small-molecule agonists that efficiently stimulate Phelipanchce aegyptiaca, and Striga hermonthica, germination in concentrations as low as 10−8 to 10−17 M. We show that full efficiency of synthetic SL agonists in triggering signaling through the Striga SL receptor, ShHTL7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…The role of SLs in inhibiting plant shoot branching has been relatively well characterized (Gomez‐Roldan et al., 2008; Wang et al., 2022). Recently, biosynthesis and signal transduction pathways of SLs have been clarified in Arabidopsis, rice and other model plants, which provides a reference for us to explore the regulation pattern of SLs on AR formation (Arite et al., 2007; Booker et al., 2005; Jiang et al., 2013; Wang, Shang, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of SLs in inhibiting plant shoot branching has been relatively well characterized (Gomez‐Roldan et al., 2008; Wang et al., 2022). Recently, biosynthesis and signal transduction pathways of SLs have been clarified in Arabidopsis, rice and other model plants, which provides a reference for us to explore the regulation pattern of SLs on AR formation (Arite et al., 2007; Booker et al., 2005; Jiang et al., 2013; Wang, Shang, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…173 Using SL-hypocotyl-shortening assays, the authors had previously identified several compounds that appeared to act as SL antagonists interacting with SL receptor ShHTL7. 174 In particular, piperazine-based analogues 207−211 have been identified as target compounds showing optimized binding into the active site of ShHTL7. For example, piperazine 211 is modified twice compared with the initial lead structure 199 carrying a p-methoxy-substituent instead of the p-fluorine and an ethoxy-substituted benzyl group replacing the N-cyclohexyl substituent.…”
Section: ■ Strigolactonesmentioning
confidence: 99%
“…Through structural analysis, the authors recognized the binding mechanism of DOZ 199 being novel and distinct from that of known SLs . Using SL-hypocotyl-shortening assays, the authors had previously identified several compounds that appeared to act as SL antagonists interacting with SL receptor ShHTL7 …”
Section: Strigolactonesmentioning
confidence: 99%
“…Weeds compete with crops for necessary resources, such as nutrients, space, light, and water, causing yield penalties of crops to 34% and more. Effective weed control methods are essential to sustainable agriculture . Using herbicides has been the most efficient approach to managing weeds .…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Effective weed control methods are essential to sustainable agriculture. 4 Using herbicides has been the most efficient approach to managing weeds. 5 Protoporphyrinogen IX oxidase (PPO, EC 1.3.3.4) has been identified as an important target for herbicide discovery during the past six decades.…”
Section: ■ Introductionmentioning
confidence: 99%